AGAMA DAN SOLIDARITAS SOSIAL: TAFSIR ANTROPOLOGI TERHADAP TRADISI RASULAN MASYARAKAT GUNUNG KIDUL DIY - Isfironi (Al'Adalah, 2013)
Modern live not always change social behavior be individual. However on the contrary give us a loyalty to traditional tenet that have communal characteristic. Traditional festival of Rasulan in Gunung Kidul Region suspicion that solidarity are preference of people in spite of the world has change. Mechanic solidarity be strong background of Popularity of this tradition in whole region. Rasulan tradition are respons of people on Gunung Kidul about modernization process that disposed neglect and disparage intimate interaction both people in public sphere that more and more limited. In a functional manner, the tradition that namely as ‘selametan’ have traditional and religion motives. Plant and harvest period are two important momentum by farmer people in Gunung Kidul. First,that is a certain that need to thank God and second as modesty expression. Rasulan tradition done alike party or festival that beginned prayer that lead by Imam. In many place done more big, even was agenda by tourism official duty of Gunung Kidul Regency. Another, done by families and them relative brother with replacement. Rasulan have been popular tradition with offering motive for destination is in order that avoided from danger live and confirm social solidarity. By rasulan tradition we can obtained meaning an social intelligent on response about aroud environment change that be able threaten social existence and social order harmoy without reject social change that impossible to avoided.